PESTLE Analysis of the Free Nutritious Meal Program Policy in Indonesia - Marnia, Marnia; Agustini, Lydia; Hardianti, Dedek; Turnip, Palentin Enjelika; Waruwu, Fridayanti; Firda, Agung Dewana (Center for Maritime Policy Governance Studies (CMPGS), 2024)
Free Nutritious Meal Program (FNMP) in Indonesia, introduced as a national initiative to combat malnutrition and improve student health outcomes, reflects a significant policy intervention within the country's broader education and health agendas. This study applies a PESTLE (Political, Economic, Social, Technological, Legal, and Environmental) analysis to critically evaluate the policy’s macro-environmental context, aiming to identify enabling and constraining factors that influence its implementation and sustainability. The primary objective is to investigate how external forces impact the effectiveness and scalability of the FNMP, particularly in diverse socio-economic and geographic regions of Indonesia. Employing a qualitative research approach, the study synthesizes policy documents, governmental reports, media sources, and relevant academic literature published between 2025. Data were coded thematically based on the six PESTLE dimensions to capture complex interdependencies affecting the policy’s rollout. The findings reveal that strong Political will and presidential backing significantly propel the program’s legitimacy and funding, while Economic challenges, such as inflation and budget reallocation, pose sustainability risks. Social, the program is well-received, especially in underprivileged areas, though disparities in community engagement remain. Technological limitations in food distribution logistics and monitoring systems are key operational barriers. Legal, the lack of binding regulatory frameworks weakens enforcement, and Environmentally, issues related to food waste and sustainable sourcing are under-addressed. In conclusion, while the FNMP holds considerable potential for improving child nutrition and educational outcomes, its long-term success depends on multi-sectoral collaboration, robust policy enforcement, and adaptive strategies.